Self-Otherings and Reimaginings of Postcolonial African Women in Chimamanda Ngozi Adichie’s Americanah (2013) - Jauza Maryam Mumtazah; Lina Meilinawati Rahayu; Ari Jogaiswara Adipurwawidjana (Universitas Sanata Dharma, 2025)
Chimamanda Ngozi Adichie’s Americanah (2013) presents a narrative that shifts between different temporalities and spaces, a movement that is particularly experienced by its main character, Ifemelu, as she navigates through her Nigerian, American, and her newly found black identity. Similarly, the novel’s narrative attempts to showcase other postcolonial African women like Ifemelu, as well as their ambiguous identities and othered representations. Through this article, we examine the workings of Ifemelu’s narration as it shifts from one space to another, specifically from Nigeria to America and vice versa, through a narratological method. We will then focus on how these specific spaces occupied by Ifemelu and other African women, or what Ogundipe-Leslie calls “women’s spaces and modes,